2019
DOI: 10.1016/j.ijrobp.2019.06.2508
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Combination Studies of an FGFR2 Targeted Thorium-227 Conjugate and the ATR Inhibitor BAY 1895344

Abstract: We report the preclinical evaluation of a combination treatment comprising a fibroblast growth factor receptor 2-targeted thorium-227 conjugate and an ATR kinase inhibitor. In vitro we observed increased potency, elevated levels of gH2AX, and inhibition of fibroblast growth factor receptor 2 etargeted thorium-227 conjugate mediated cell cycle arrest as a result of the combination. In vivo efficacy Purpose: Fibroblast growth factor receptor 2 (FGFR2) has been previously reported to be overexpressed in several t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…To test this hypothesis, several preclinical studies have been performed where TTCs were combined with DDR inhibitors. [84][85][86] A humanized HER2-targeting IgG1 antibody derived from trastuzumab was conjugated to the 3,2-HOPO chela-tor and subsequently radiolabeled with 227 Th resulting in HER2-TTC. 25 Robust tumor growth inhibition was achieved when HER2-TTC was combined at a subefficacious monotherapy dose of 125 kBq/kg with the poly-ADP ribose polymerase 1/2 (PARP1/2) inhibitor olaparib in the DLD-1 BRCA2 -/xenograft model established from the DLD-1 colorectal cancer cell line with inactivated BRCA2 gene, while no significant tumor inhibition occurred in the xenograft model established from the DLD-1 parental isogenic cell line (Table 2).…”
Section: Rationale For Combining Ttcs With Inhibitors Of Ddrmentioning
confidence: 99%
See 3 more Smart Citations
“…To test this hypothesis, several preclinical studies have been performed where TTCs were combined with DDR inhibitors. [84][85][86] A humanized HER2-targeting IgG1 antibody derived from trastuzumab was conjugated to the 3,2-HOPO chela-tor and subsequently radiolabeled with 227 Th resulting in HER2-TTC. 25 Robust tumor growth inhibition was achieved when HER2-TTC was combined at a subefficacious monotherapy dose of 125 kBq/kg with the poly-ADP ribose polymerase 1/2 (PARP1/2) inhibitor olaparib in the DLD-1 BRCA2 -/xenograft model established from the DLD-1 colorectal cancer cell line with inactivated BRCA2 gene, while no significant tumor inhibition occurred in the xenograft model established from the DLD-1 parental isogenic cell line (Table 2).…”
Section: Rationale For Combining Ttcs With Inhibitors Of Ddrmentioning
confidence: 99%
“…However, the potency of the combination was further enhanced in the DLD-1 BRCA -/model due to DNA DSB repair deficiency FGFR2-TTC ATRi 85 MSLN-TTC FGFR2-TTC demonstrated increased potency in combination with ATRi when both agents were administered at subefficacious doses in mice bearing MFM-223 tumors (TNBC) Respective monotherapies did not show tumor growth inhibition at the same doses MSLN-TTC demonstrated synergistic activity when combined with ATRi at subefficacious doses in mice bearing OVCAR-3 tumors (ovarian cancer) ATRi and olaparib 86 Similarly, MSLN-TTC demonstrated additive activity when combined with olaparib at subefficacious doses in mice bearing OVCAR-3 tumors (ovarian cancer) Respective monotherapies did not show tumor growth inhibition at the same doses ATRi, inhibitor of ataxia telangiectasia and Rad3-related; DSB, double-strand break; FGFR2, fibroblast growth factor receptor 2; HER2, human epidermal growth factor receptor 2; MSLN, mesothelin; TNBC, triple-negative breast cancer; TTC, targeted thorium-227 conjugate. treatment.…”
Section: Rationale For Combining Ttcs With Inhibitors Of Ddrmentioning
confidence: 99%
See 2 more Smart Citations
“…108 The same group of investigators have also reported on the potential utility of 227 Th conjugates targeting the fibroblast growth factor receptor 2 (FGFR2), which is overexpressed in many cancers, and in acute myeloid leukemia targeting CD33. 109,110 212 Pb…”
Section: Preclinical Studiesmentioning
confidence: 99%